Mapeamento de competências de profissionais de planejamento por cenários - Mendes Junior, Djalma Gomes (2023)
The large-scale replacement of human work by machines increasingly leads to new ways of using information, often acting directly on human interaction. In this evolution, companies need multidisciplinary professionals with strategic skills. The construction of scenarios is a tool used directly in the strategic planning process of organizations, being a fundamental piece for their leaders to reposition their strategies with a view to achieving their objectives. The research sought to establish studies related to the training process of professionals who perform the activities of creating prospective scenarios for use in the strategic planning of organizations. The general objective of the work is to present a mapping of competences of professionals who work in the area of planning by scenarios, taking into account the main applied theories, based on the model of people management by competences and the contributions to the planning activity by scenarios. The methodology used consisted of identifying key competencies through the literature. 4 basic functions that make up the teams were identified, then a questionnaire was proposed for each specialty with the aim of validating and measuring the identified competences, finally a competence matrix was elaborated for professionals who work in scenario planning. The work reached a ratio of 31 basic skills for professionals who work in scenario planning.